Growth performance, digestibility, and blood biochemical parameters of Nile tilapia (Oreochromis niloticus) reared in floating cages and fed poultry by-product meal. Issue 1 (2nd January 2020) - Palupi, Esti Tuhu; Setiawati, Mia; Lumlertdacha, Sonkphan; Suprayudi, Muhammad Agus
ABSTRACT: A 120-day feeding trial was conducted in floating cages to evaluate growth performance and digestibility of Nile tilapia ( Oreochromis niloticus ) juveniles fed diets containing different levels of poultry by-product meal (PBM) as a replacement for fishmeal. Nile Tilapia with an average body weight of 56.6 ± 0.28 g were used in this experiment. Five diets were formulated to contain graded levels of PBM at 0%, 5%, 10%, 20%, and 30% poultry by-product meal (PBM) and are referred as PBM0, PBM5, PBM10, PBM20, and PBM30, respectively. Groups of 25 Nile tilapia were fed close to the apparent satiation, three times a day. The results showed that growth performance, survival and whole-body composition for fish fed the experimental diets were not significantly different (P > .05) than fish fed the control diet. Apparent digestibility of dry matter, protein, lipid and amino acids of fish fed the PBM20 and PBM30 were lower compared to the other treatments (P < .05). The PBM dietary levels significantly lowered total protein, high-density-lipoprotein (HDL) and cholesterol concentration. The results of this study indicated that good quality PBM can be used up to 30% in commercial diets for Nile tilapia without any adverse effect.